Strange, Unusual, and Creative Sentences: Analyzing “Outside the Box” Criminal Sentencing - Heumann, Milton (Victims & offenders, 2023)
This is an exploratory study of “non-traditional” criminal punishments, particularly focusing on the attitudes toward these sentences among prosecutors, defense attorneys, and judges. Through interviews with practitioners, this study explores among other things, if they had used, or advocated for, these types of sentences and why or why not. There was a broad openness to doing something different from the status quo of fine or jail, however it was tempered by concerns of bias and fairness. With considerations of mass incarceration dominating the reform conversation, we find that openness to individualizing sentences, albeit with “guardrails,” is reentering the reform conversation.